Discovery of a new autophagy inducer for A549 lung cancer cells. Issue 13 (1st July 2019) - Li, Na; Qu, GuoJing; Xue, JingNa; Li, Xiao; Zhao, Xuan; Yan, YeHao; Gao, DongFang; Zhang, Lu; Wang, Peng; Zhang, Ming; Zhao, BaoXiang; Miao, JunYing; et al.
Graphical abstract: Highlights: The activity of a series of fluorescent compounds was investigated. Compounds8 and11 reduced the cell viability of A549 lung cancer cells. Compound8 inhibited the activity of mTOR. Co mpounds8 and11 induced apoptosis and autophagy. Co mpound8 induced autophagy with intact autophagic flux. Abstract: Biological activities of a series of fluorescent compounds against human lung cancer cell line A549 were investigated. The results showed that ( E )-1, 3, 3-trimethyl-2-(4-(piperidin-1-yl)styryl)-3H-indol-1-ium iodide (8 ) and ( E )-2-(5, 5-dimethyl-3-(4-(piperazin-1-yl)styryl)cyclohex-2-en-1-ylidene) malononitrile (11 ) could inhibit the growth of A549 cancer cells in a dose and time-dependent manner. Furthermore, compound8 could trigger autophagy and apoptosis, but not obviously induce necrosis under the stimulatory condition. Therefore, 8 can be used as autophagy activator to investigate the regulatory mechanism of autophagy and may offer a new candidate for the treatment of lung cancer.